Efficiency of State Transport Undertakings: A Case Study of Pepsu Road Transport Corporation (PRTC) - Goyal , Munish; Bansal, S.K. (Gyan Management Journal, 2011)
An efficient transport system is absolutely necessary for sustaining other crucial economic activities. Improving the quality of public transport services would require restructuring the State Transport Undertakings (STUs) also, as these are the major service provider of passenger road transport. Hence, there is a need to review various operational and financial aspects of STUs. First phase of the study discusses the position of manpower productivity in PRTC (One of the major state transport undertaking (STU) operating in Punjab). In the second phase, development of human resources in transport industry, such as human resource planning, training, motivation, performance appraisals, merit rating, rewarding and compensation methods have been dealt Findin9s of the study will further help the STUs to formulate an appropriate strategy for the optimum utilization of its manpower.